Investigating The Perceived Effects of Starting a Second FL on Hungarian EFL Learners - Kürtös, Adria Mária (Working Papers in Language Pedagogy, 2022)
Learning a foreign language (FL) in itself is emotionally challenging for learners demanding substantial motivation on their behalf. Learning two FLs in parallel might only increase the number of obstacles to overcome. The present qualitative research aims at discovering the possible effects of starting a new FL on 18-19-year-old Hungarian English as a Foreign Language (EFL) students. The data analysis revealed that the introduction of a second foreign language (FL2) did have an impact on students’ EFL learning in most cases and resulted in changes in their language learning motivation and emotions towards their FLs. Based on students’ attitudes these changes were identified as four different emerging themes. Overall, it may be stated that students’ language learning motivation and emotions seemingly depended on their previous EFL learning experiences and on their reception of the FL2. It can be concluded that none of the students mentioned that they had managed to acquire both FLs at a desired level before the data collection, and none of them described the same positive attitude towards learning the two FLs.